The Correlation between Physical Workload and the Increase in Workers’ Pulse Rate - Elsya Vira Putri (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: The workload that exceeds individual work capacity will increase the pulse rate rapidly. The purpose of this research was to study the correlation between physical workload and the increase in workers’ pulse rate. Methods: This research utilized cross-sectional design by using the observational method with 23 workers from the BRF area of PT X Sidoarjo as respondents. This research was conducted by conducting the direct observation by calculating the workload received by the worker by using %CVL method and calculating the resting and working heart rates. Results: The result showed that all workers were male and had the productive age distribution of 60.9% in the age range of 25-50 years. Based on the calculation of workload, the majority of workers have the workload on the moderate %CVL category, amounting to 56.5%. Based on the measurement of the resting and working heart rates, it was found that all workers experienced the pulse rate increase. Based on the result of Pearson correlation statistical test, the result was p<0.05, which means that there was a significant correlation between the workload and the increase in the workers’ pulse rate. Moreover, the correlation coefficient was 0.911, that indicated a very strong and positive correlation. Conclusion: This research concludes that there is a strong and positive correlation between workload and the increase in the workers’ pulse rate. Keywords: %CVL, cardiovascular load, workload, pulse rate